ON DISCRETE WEIGHTED STATISTICAL CONVERGENCE - Ercan, Sinan; Altin, Yavuz; Colak, Rifat (Univ Nis, 2020)
In the present paper, the notion of discrete weighted mean method of summability have been extended over the concept of statistical convergence. We have also given the notion of statistical (M, P-lambda)- summability and [M, P-lambda](q)-summability. We have introduced some properties of these modes of convergence.
Keywords: statistical convergence; weighted statistical convergence; statistical ((N)over-bar, p(n))-summability